Bery Engebretsen letter to Thomas H. Kent regarding fall bird sightings, December 5, 1998 - Engebretsen, Beryet al (1998)
Letter from Bery Engebretsen to Thomas H. Kent regarding fall bird sightings, December 5, 1998. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed/flatbed